Interdigital Neuroma in the Second Intermetatarsal Space Associated with Metatarsophalangeal Joint Instability - Matsumoto, Takumi (Case Rep Orthop, 2016)
The entrapment theory is the most commonly accepted theory concerning the development of interdigital neuroma; it incriminates the deep transverse metatarsal ligament as the major causative factor of the condition. This report presents a patient with interdigital neuroma in the second intermetatarsal space, which was strongly suspected to be caused by the metatarsophalangeal joint instability due to plantar plate injury. Surgical intervention revealed that the neuroma was located more distally and dorsally than the deep transverse metatarsal ligament and was pinched between the adjacent metatarsal heads, suggesting the involvement of the metatarsophalangeal joint instability and chronic trauma as etiologies in this case.